Assessing Malaysia Marine Fisheries Sustainability Under Climate Change Pressure: A Quintuple Helix Approach - Rahmat, Siti Rahyla (2019)
Marine fisheries are a major industry in Malaysia fisheries sector, which contributes significant growth in the economy and national food security. Unfortunately, this industry is vulnerable to the threats of climate change in relation to the marine environment such as the rising sea level, water acidity, and sea surface temperature. This study aims to assess the impact of climate change on the sustainability of marine fisheries in Malaysia. This study uses Quintuple Helix model approach which is the expansion of the established Triple Helix sustainability model that includes climate change as one of the important indicators. It involves a time-series analysis from 1989 to 2018 using Auto-Regressive Distribution Lag (ARDL). A long and short-run impact from rising in temperature and sea level on marine fisheries sustainability will help to impose a better adaptation and mitigation strategy for this industry. Consequently, the sustainability of marine fisheries will secure national economic prosperity and healthy protein supply.